2008
DOI: 10.1007/s11255-008-9385-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of preoperative testicular volume in Japanese children with unilateral cryptorchidism

Abstract: From the viewpoint of undescended testicular volume, cryptorchid children should be operated on as early as possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
(23 reference statements)
1
3
0
Order By: Relevance
“…In the present study, we found a significant decrease in the echogenicity and volume in patients with UDT compared to the healthy group and the healthy side. Our findings were thus found to be compatible with the previous literature ( 21 , 22 , 23 ) . Both conventional methods of measuring testicular volumes and the novel SWE-based method were utilized in our study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, we found a significant decrease in the echogenicity and volume in patients with UDT compared to the healthy group and the healthy side. Our findings were thus found to be compatible with the previous literature ( 21 , 22 , 23 ) . Both conventional methods of measuring testicular volumes and the novel SWE-based method were utilized in our study.…”
Section: Discussionsupporting
confidence: 93%
“…However, there have been many disagreements among scientists, with some claiming that these methods are not reliable enough to accurately determine the relationship between the volume of the testes and testicular histology ( 17 , 18 ) . Histopathological examination of UDT revealed a significant decrease in the number of germ cells and Leydig cells; progressive reduction in the size of the seminiferous tubules followed by peritubular fibrosis ( 6 , 19 , 20 , 21 , 22 ) . Numerous reported studies have shown that these histopathological alterations cause a significant reduction in the volume of the UDT ( 23 , 24 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have reported a weak correlation between testicular size at orchiopexy, and lower ratios of paternity, hormone levels, sperm count and testicular volume in adult patients ( 45 , 46 ). According with others, we found a strong positive correlation between lower FSH levels (a marker of spermatogenesis) and high location of the testicle ( 9 , 47 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Testicular volumes were calculated assuming the testes to be ellipsoidal (4/3π×length×width×depth). 11 Boys with peeping and gliding testes were included in the abdominal and inguinal testes groups, respectively.…”
Section: Methodsmentioning
confidence: 99%